Criterion Validity of the Yale-Brown Obsessive-Compulsive Scale Second Edition for Diagnosis of Obsessive-Compulsive Disorder in Adults - Castro-Rodrigues, Pedro; Camacho, Marta; Almeida, Sílvia; Marinho, Mónica; Soares, Catarina; Barahona-Corrêa, J. Bernardo; Oliveira-Maia, Albino J. (Frontiers in Psychiatry, 2018)
Background: While the Yale-Brown Obsessive-Compulsive Scale Second Edition (Y-BOCS-II) is the gold-standard for measurement of obsessive-compulsive (OC) symptom severity, its factor structure is still a matter of debate and, most importantly, criterion validity for diagnosis of OC disorder (OCD) has not been tested. This study aimed to clarify factor structure and criterion validity of the Y-BOCS-II. Methods: We first validated and quantified the psychometric properties of a culturally adapted Portuguese translation of the Y-BOCS-II (PY-BOCS-II). The PY-BOCS-II and other psychometric instruments, including the OCD subscale of the Structured Clinical Interview for the DSM-IV, used to define OCD diagnosis, were administered to 187 participants (52 patients with OCD, 18 with other mood and anxiety disorders and 117 healthy subjects). In a subsample of 20 OCD patients and the 18 patients with other diagnoses Y-BOCS-II was applied by clinicians blinded to diagnosis. Results: PY-BOCS-II had excellent internal consistency (Cronbach’s α=0.96) and very good test-retest reliability (Pearson’s r=0.94). Exploratory factor analysis revealed a two-factor structure with loadings consistent with the Obsessions and Compulsions subscales, and there was good to acceptable convergent and divergent validity. Importantly, the area under the curve (AUC) of the receiver operating characteristics (ROC) curve suggested elevated accuracy in discriminating between patients with OCD and control subjects (AUC=0.96; 95% confidence interval [CI]: 0.92 - 0.99), that was retained in comparisons with age, gender and education matched controls (AUC=0.95; 95% CI: 0.91 - 0.99), as well as with patients with other mood and anxiety disorders (AUC=0.93; 95% CI: 0.84 - 1). Additionally, a cut-off score of 13 had optimal discriminatory ability for the diagnosis of OCD, with sensitivity ranging between 85 and 90%, and specificity between 94% and 97%, respectively when all samples or only the clinical samples were considered. Conclusion: The PY-BOCS-II has excellent psychometric properties to assess the severity of obsessive-compulsive symptoms, reflecting obsessive and compulsive dimensions, compatible with currently defined subscales. Furthermore, we found that a cut-off of 13 for the Y-BOCS-II, total score has good to excellent sensitivity and specificity for the diagnosis of OCD.